Disulfiram Alone Functions as a Radiosensitizer for Pancreatic Cancer Both In Vitro and In Vivo - Xu, Ying; Lu, Lunjie; Luo, Judong; Wang, Lili; Zhang, Qi; Cao, Jianping; Jiao, Yang (Frontiers in Oncology, 2021)
The prognosis of pancreatic cancer remains very poor worldwide, partly due to the lack of specificity of early symptoms and innate resistance to chemo-/radiotherapy. Disulfiram (DSF), an anti-alcoholism drug widely used in the clinic, has been known for decades for its antitumor effects when simultaneously applied with Copper ion, including pancreatic cancer. However, great controversy still exists in the context of the antitumor effects of DSF alone in pancreatic cancer and related mechanisms, especially in its potential roles as the sensitizer for cancer radiotherapy. In the present study, we focused on whether and how DSF could facilitate ionizing radiation (IR) to eliminate pancreatic cancer. It was showed that DSF by itself can significantly suppress the survival of pancreatic cancer cells after exposure to IR, both in vitro and in vivo. Additionally, DSF treatment alone can cause DNA double-strand breaks (DSBs) and further enhance IR-induced DSBs in pancreatic cancer cells. In addition, DSF alone boosted IR-induced cell cycle G2/M phase arrest, as well as apoptosis in pancreatic cancer exposed to IR. By applying RNA sequencing and bioinformatics analysis, it was suggested that DSF might trigger cell adhesion molecule (CAM) signaling, which might be involved in its function in regulating the radiosensitivity of pancreatic cancer cells. In conclusion, we suggested that DSF alone might function as a radiosensitizer for pancreatic cancer, probably by regulating the IR-induced DNA damage, cell cycle arrest and apoptosis, at least partially through CAM signaling pathway.